2023
DOI: 10.1186/s12967-023-04584-8
|View full text |Cite
|
Sign up to set email alerts
|

The complexity of nicotinamide adenine dinucleotide (NAD), hypoxic, and aryl hydrocarbon receptor cell signaling in chronic kidney disease

Colleen S. Curran,
Jeffrey B. Kopp

Abstract: Early-stage detection of chronic kidney diseases (CKD) is important to treatment that may slow and occasionally halt CKD progression. CKD of diverse etiologies share similar histologic patterns of glomerulosclerosis, tubular atrophy, and interstitial fibrosis. Macro-vascular disease and micro-vascular disease promote tissue ischemia, contributing to injury. Tissue ischemia promotes hypoxia, and this in turn activates the hypoxia-inducible transcription factors (HIFs). HIF-1α and HIF-2α, share a dimer partner, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 157 publications
0
4
0
Order By: Relevance
“…Of particular importance is the maintenance of the NAD + pool through 3 major pathways in kidney cells. It may have implications for our findings: (a) the sodium-monocarboxylate transport (Preiss-Handler pathway), (b) the salvage pathway, and (c) de novo biosynthesis ( 49 51 ). It is noteworthy that the preservation of ETC integrity induced by Dapa in our study is likely associated with the restoration of the NAD + /NADH ratio, since these proteins favor the oxidized form of this coenzyme ( 47 ).…”
Section: Discussionmentioning
confidence: 87%
“…Of particular importance is the maintenance of the NAD + pool through 3 major pathways in kidney cells. It may have implications for our findings: (a) the sodium-monocarboxylate transport (Preiss-Handler pathway), (b) the salvage pathway, and (c) de novo biosynthesis ( 49 51 ). It is noteworthy that the preservation of ETC integrity induced by Dapa in our study is likely associated with the restoration of the NAD + /NADH ratio, since these proteins favor the oxidized form of this coenzyme ( 47 ).…”
Section: Discussionmentioning
confidence: 87%
“…Based on the author’s knowledge, there is no available literature to date with direct evidence of NAPRT’s influence on cardiac health. But the research on other applications including cancer [ 51 ], sepsis/septic shock [ 52 ], and treatment in prostate, ovarian, colorectal, and pancreatic disease [ 53 55 ] showed great potential. However, NAPRT appears as a driver in inflammatory processes to control the activation of macrophages necessary to recover from acute inflammatory diseases such as sepsis and septic shock [ 56 ].…”
Section: The Biological Significance Of Naprt In Cardiac Healthmentioning
confidence: 99%
“…The combined role of NAMPT and NAPRT in inflammation was also observed [ 49 ]. Another study on colorectal cancer (CRC) showed that the duration of disease-free survival time and overall survival time from CRC is indicated by NAMPT or NAPRT expression and the excessive level of NAMPT/NAPRT indicates the improper prognosis of patients with CRC in a distinct mechanism [ 52 ]. There are several research groups already working to find out the combined effect of NAMPT and NAPRT in different clinical domains, but to date, no conclusive data are available related to the combined effect on cardiovascular application.…”
Section: The Combined Effect Of Nampt and Naprtmentioning
confidence: 99%
“…During AKI, β-oxidation decreases and ATP synthesis is compensated through aerobic glycolysis (insufficient to meet NADH and FADH 2 cofactor requirements), followed by anaerobic glycolysis (leading to lactate synthesis). Activation of the HIF-1α factor and activation of AhR [175] and mitochondrial dysfunction [176] are both causes and consequences of the transition from normoxic to anaerobic metabolism. In addition, the processes involved in the progression of renal pathology (collagen deposition, chronic inflammation, etc.)…”
Section: Metabolic Reprogramming In the Aki-to-ckd Transitionmentioning
confidence: 99%